Impact of the global economic crisis on Taipei, China's industrial structure and firm activity - Jack W. Hou (Asian Development Bank Institute (ADBI), 2011)
Confronted by the current global economic crisis, Taipei, China's economy has suffered much like its neighbors. However, Taipei, China is different from other East Asia economies in several aspects. First, Taipei, China's industrial organization is dominated by small and medium-sized enterprises (SMEs), unlike the chaebols of the Republic of Korea or the Japanese Kabushiki-gaish. Second, Taipei, China has experienced extraordinary hollowing-out of its industrial base as many firms (both large and SMEs) have moved their manufacturing operation to People's Republic of China (PRC). This is also manifested in the fact that Taipei,China has become one of the largest sources of FDI in the PRC, and Taipei, China's trade dependency with the PRC is ever rising. A silver lining is that when the sub-prime crisis hit the United States and weakened her import demand, the aforementioned hollowing-out meant less direct employment impact on Taipei, China. However, given the dominance of SMEs in Taipei, China (97.6% of business establishments, and 77.1% of employment), it is of vital importance to develop ways to aid SMEs in surviving this crisis. Indeed, the government can utilize this crisis to reform and strengthen SMEs so they can continue to be the backbone of Taipei, China's economy. In this paper, I discuss the strengths and weaknesses of SMEs in Taipei,China. Policy recommendations are presented to address the weaknesses of the SMEs, including short-run and long-run approaches.
Keywords: G01; G10; F14; O53; 330; Wirtschaftskrise; Weltkonjunktur; Makroökonomischer Einfluss; Klein- und Mittelunternehmen; Industriestruktur; Taipeh; China